Regulation and governance for the implementation and management of point-of-care testing in Australia: a scoping review - Jacqueline Prestedge; Claire Kaufman; Deborah A. Williamson (BMC Public Health)
Abstract Background Point-of-care testing (PoCT) is an increasingly important diagnostic tool in the healthcare system for accessible pathology testing in hospital, primary care, and community care settings. Clear regulation and governance models are important to ensure quality of PoCT results for patient care. Methods This review aimed to identify existing regulation and guidelines for management of PoCT and how this has been implemented within Australian healthcare services. We conducted a search of academic publications in PubMed and grey literature (national, state, and independent organisations) and other publicly available information from internet searches for governance of PoCT in Australia. Relevant data from these sources were extracted and narratively synthesised. Results Forty-seven sources (17 studies from PubMed, 30 grey literature) were included in the final review. Of the grey literature sources, fifteen current PoCT governance documents comprising of six standards, five guidelines and four frameworks at the international, national and jurisdictional level were included with an increasing number of grey literature sources since the onset of the COVID-19 pandemic in 2020. The seventeen included research articles were categorised according to implementation barriers and facilitators with the themes of workforce, clinical governance, PoCT workflow, and cost. An understanding of the clinical and cultural context for PoCT was the most frequently reported facilitator of PoCT, while the most frequently reported barrier was related to inadequate data management. Conclusion This review demonstrated limited and inconsistent sources on regulatory and governance models for implementing and managing PoCT in Australia. Identified PoCT programs showcased diverse implementation and governance models to support quality PoCT, with few reporting formal accreditation. Streamlined, practical regulation and governance for PoCT may increase adoption across healthcare settings while ensuring quality results and meeting the needs of patients and healthcare practitioners.